PT. KERETA API INDONESIA (PERSERO) DAERAH OPERASI VIII SURABAYA MENERAPKAN PRINSIP GCG - JAYANTI, PIPUT DWI; Praptoyo, Sugeng (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
This research is meant to examine whether the implementation of Good Corporate Governance on PT. Kereta Api Indonesia (Persero) Daerah Operasi VIII Surabaya has been manifested properly in order to find out the problems which are encountered by PT. Kereta Api Indonesia (Persero) Daerah Operasi VIII Surabaya in implementing the principles of Good Corporate Governance. Result of this research obtained that the implementation of Good Corporate Governance on PT. Kereta Api Indonesia (Persero) Daerah Operasi VIII Surabaya has been manifested properly based on the transparency principle, accountability, responsibility, independency, and fairness. Moreover, it has been found that there are no meaningful problems in implementing of Good Corporate Governance principles.Keywords: Good Corporate Governance, Transparency, Accountability, Responsibility, Independency, and Fairness.